Discretionary Accounting Choice and Management Opportunistic Behavior to Manage Income - Theresia Trisanti (Jurnal Akuntansi dan Keuangan, 2019)
Income smoothing (IS) practice is "the smoothing of fluctuations company income levels that are considered normal for company". IS manipulation has a clear goal, which is to generate income flows that continue increase stably. There are several ways that companies can use to do IS practice for example: changes in accounting methods. In this research, income smoothing practices of Indonesian listed manufacturing firms were detected through empirical tests using changes in discretionary accounting (DAC). Samples of listed manufacturing companies classified as smoothing and non-smoothing using Moses smoothing behavior index. The results show that the possible motivation of DAC transactions is income smoothing. Two independent variables such as institutional ownership and external audit quality have a significant positive effect on IS practice but the company size has no influence on IS practice.